Clinically relevant enantiomer specific R‐ and S‐praziquantel pharmacokinetic drug‐drug interactions with efavirenz and ritonavir - Chenai Sheilla Mutiti; Nyasha Nicole Kapungu; Comfort Ropafadzo Kanji; Nadina Stadler; Julia Stingl; Charles Nhachi; James Hakim; Collen Masimirembwa; Roslyn Stella Thelingwani (Wiley, 2021)
Abstract We conducted a clinical study to determine the effect of efavirenz and ritonavir on the pharmacokinetics of R‐ and S‐PZQ in healthy male participants. This was toward evaluating the risk of drug‐drug interactions, which may occur after PZQ administration to HIV patients on efavirenz or ritonavir containing regimens. A non‐randomized, open‐label, single‐dose, one sequence crossover study with 2 arms was conducted. We gave 26 healthy volunteers a single oral dose of 40 mg/kg PZQ followed by a daily oral dose of either 400 mg efavirenz or 100 mg ritonavir for 14 consecutive days. On day 14, they ingested a single 40 mg/kg dose of PZQ. We measured plasma levels up to 12 h on day 1 and day 14. Samples were analyzed by LC‐MS. Pharmacokinetic analysis was conducted in WinNonlin to determine the primary endpoints (plasma T1/2, Cmin, and AUC). Efavirenz had a significant effect on the pharmacokinetics of PZQ (p < .05), reducing the AUC by 4‐fold (1213.15 vs. 281.35 h·ng/ml for R‐PZQ and 5669 vs. 871.84 h·ng/ml for S‐PZQ). Ritonavir had no significant effect on R‐PZQ but increased the AUC 2‐fold for S‐PZQ (p < .05) (4154.79 vs. 7291.05 h·ng/ml). Using PZQ in HIV patients needs investigation, as there is a risk of both treatment failure and adverse effects because of induction and inhibition, respectively.